Safety, tolerability and pharmacokinetics of WXFL10203614 in healthy Chinese subjects: A randomized, double-blind, placebo-controlled phase Ⅰ study - Huang, Kai; Ding, Ying; Que, Linling; Chu, Nannan; Shi, Yunfei; Qian, Zhenzhong; Qin, Wei; Chen, Yuanxin; Gu, Xianghong; Wang, Jiakun; Zhang, Zhiwei; Xu, Jianguo; et al. (Frontiers in Pharmacology, 2022)
Abstract Objective: This study was conducted to investigate the safety, tolerability and pharmacokinetics (PK) of WXFL10203614 after single and multiple oral doses in healthy Chinese subjects. Methods: A single-center, randomized, double-blind, placebo-controlled phase Ⅰ study was performed on healthy Chinese subjects. In the single-dose study, Subjects were randomized into 7 dose levels of WXFL10203614 (1 mg group, n=2; 2, 5, 10, 17, 25 and 33 mg groups with placebo, 8 subjects per group, 2 of them given placebo). In the multiple-dose study, subjects received 5 or 10 mg WXFL10203614 once daily (QD), 5 mg twice daily (BID) or placebo for 7 consecutive days. Safety, tolerability and PK of WXFL10203614 were all assessed. Results: A total of 592 subjects were screened, 50 subjects were enrolled in the single-dose study and 30 in the multiple-dose study. All adverse events (AEs) were mild or moderate and resolved spontaneously. No Serious Adverse Events (SAEs) or deaths were reported during the study. WXFL10203614 was absorbed rapidly after dosing with Tmax of 0.48-0.98 h, Cmax, AUC0-t and AUC0-∞ were all increased in a dose-related manner over the range of 1-33 mg. Renal excretion was the major route of elimination of WXFL10203614. Steady-state PK parameters (Cmax,ss, AUC0-t,ss and AUC0-∞,ss) were elevated after once-daily administration of 5-10 mg WXFL10203614 and non- and weak drug accumulations were observed, whereas moderate drug accumulation occurred in the 5 mg BID group. Conclusion: WXFL10203614 exhibited good safety, tolerability and favorable PK profiles in healthy Chinese subjects, supporting further clinical development in patients with rheumatoid arthritis. Clinical trials registration number: http://www.chinadrugtrials.org.cn/index.html # CTR20190069 and CTR20200143